Estrategias lúdicas para la convivencia de los niños del subnivel 2 de la Unidad Educativa las Américas, Ciudad de Riobamba. - Ramos Saca, Lisbeth Estefania (2024)
The present research work is titled; "Playful Strategies for the Coexistence of Children from Sublevel two of the Educational Unit of the Americas" of the City of Riobamba, Chimborazo Province. Its objective is to determine recreational strategies for the coexistence of children in sublevel 2, and together with this objective, three specific ones were formed, which are supported by the development of the theoretical framework: This talks about the importance of implementing strategies and recreational activities for children's school coexistence. That said, the research also focuses on cooperative games since they are a handy tool for the socialization of children in their environment. A nonexperimental study was carried out based mainly on a descriptive review of books and documents. This allowed us to see the importance of using playful strategies for the coexistence of children at the initial level. To collect information, an observation sheet was applied to fifteen students, six boys and nine girls, in which different activities were taught, and they were evaluated through observation. After the analysis and interpretation of results and tabulation, it was evident that most children are interested in learning to carry out recreational activities and games that allow them to live and interact with their peers healthily. For instance, [specific example of a result and its interpretation]. However, it is essential to mention that recreational activities were selected and carried out that favor the school coexistence of children at the initial level. It is worth noting that the teacher can apply these games and recreational activities during the teaching-learning process of the school year.